Asymptotic stress field at the tip of an inclined crack terminating to an interface - Liviu Marsavina; Tomasz Sadowski (Budownictwo i Architektura, 2008)
This paper presents the numerical results for the asymptotic stress field and the fracture parameters at the tip of an inclined cracks terminating to a bi-material ceramic interface. The numerical analysis was carried out using FRANC2D/L fracture analysis code. A biaxial specimen was modeled for producing different mixed mode loads and two materials combinations of Al2O3 and ZrO2 were considered. The influence of the material combination and applied mixed mode load on the singularity orders, stress distributions and stress intensity factors is highlighted.